PERCEPTIONS AND ATTITUDES OF THE STUDENTS OF YUAN ZE UNIVERSITY ABOUT THE USE OF BIOGAS PRODUCED BY HUMAN WASTE - François, Mathurin (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2020)
ABSTRACT Energy demand is increasing following the expansion of the world population. Approximately 1.1 billion people worldwide do not have access to electricity, mostly living in developing countries. This article aimed to evaluate the perception of the students of Yuan Ze University about the use of biogas produced from human waste. A sample of 110 students from different faculties of the university was randomly chosen to be interviewed on this subject through a questionnaire with both closed and opened questions. The analysis of the data was processed with the R software in order to calculate the p-value of the questions and socio-demographic data, with the significant level set at 0.05. This work found that 54.5% of the students have already heard that human waste can be used to produce biogas, while 89.1% of the respondents thought this alternative is possible. When asked whether they would use this gas, the percentage dropped to 55.5%. Most of the students stated that they would use only biogas produced with their own excreta (52.0%). The main barriers presented by the respondents for not using this gas were health risk (40.0%), bad smell (26.4%), and fear (10.9%). This work found that the use of human waste in the production of biogas was regarded as a viable alternative by the students of Yuan Ze University, with health risk being the major concern. PERCEPÇÕES E ATITUDES DOS ESTUDANTES DA UNIVERSIDADE YUAN ZE EM RELAÇÃO DO USO DO BIOGÁS PRODUZIDO PELA EXCRETA HUMANA RESUMO A medida que a população mundial aumenta, com ela cresce a demanda de energia. Cerca de 1,1 bilhão de pessoas no mundo não houveram acesso a eletricidade. A maioria deles vive em países em desenvolvimento. Este artigo teve como objetivo avaliar a percepção dos estudantes da Universidade Yuan Ze sobre o uso de biogás proveniente de excreta humana. Um total de 110 estudantes de diferentes faculdades foi escolhido aleatoriamente para ser entrevistado sobre esse assunto, por meio da utilização de questionário com perguntas fechadas e abertas. A análise dos dados foram processadas no software R para calcular o valor-p, a fim de determinar o nível significativo estabelecido em 0,05 para as perguntas e as características sociodemográficas. Constatou-se que 54,5% dos estudantes já ouviram falar que a excreta humana pode ser usada para produzir biogás, 89,1% dos entrevistados pensaram que essa alternativa é possível. Quando perguntados se usariam esse gás, o percentual caiu para 55,5%. A maioria dos estudantes afirmou que usaria apenas biogás produzido com suas próprias excretas (52,0%). As principais barreiras apresentadas pelos entrevistados para não usar esse gás foram risco à saúde (40,0%), mau cheiro (26,4%) e medo (10,9%). Conclui-se que o uso de excremento humano na produção de biogás foi visto como uma alternativa viável pelos estudantes da Universidade Yuan Ze, mas o risco à saúde foi a maior preocupação deles.